Лазеры на парах металлов с индукционным нагревом рабочей зоны; Оптика атмосферы и океана; Т. 31, № 3 - Тригуб М. В. Максим Викторович; Федоров В. Ф. Валерий Федорович; Шиянов Д. В. Дмитрий Валерьевич; Евтушенко Г. С. Геннадий Сергеевич (2018, 2018)
Заглавие с экрана